If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-4x + 8y) + -12y = 0 (-4x * 3 + 8y * 3) + -12y = 0 (-12x + 24y) + -12y = 0 Combine like terms: 24y + -12y = 12y -12x + 12y = 0 Solving -12x + 12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. -12x + 12y + -12y = 0 + -12y Combine like terms: 12y + -12y = 0 -12x + 0 = 0 + -12y -12x = 0 + -12y Remove the zero: -12x = -12y Divide each side by '-12'. x = y Simplifying x = y
| 13+7x-5(2x+18)=3x+2(x-5) | | (4x-1)+113=180 | | p+6=12.5 | | 2(5-8x)-5=-5(2x+1) | | 2(4Y-1)=8 | | a=2x+5(2x) | | -0.4*(3x-1)+8*(0.8x-0.3)=5-(3.8x+4) | | 7e+4e-e+3e= | | 35+7d=175 | | 6m+3=24 | | 209=m-354 | | 2(2X+10)=80 | | 3g=237 | | -2.4-4x-8.6-2x=-5x-7.3 | | 6p+3p-p= | | 9-5z=4 | | 2m^2-11m-115=6 | | -1.2x+0.4+6.4x-2.4=5-3.8x+4 | | 5z(-9)=4 | | 9h+h+2h= | | y^3-5y+5=0 | | 2x+3=-12x+1 | | (5x+4)=56 | | X=150-.2x | | -2-3+4=5-6x | | 10x-5-3(2x+5)=-20 | | 2(2x-5)+6(2x+6)=0 | | 9m-26=36 | | 25x^2+4y^2-6=0 | | f(0)=2(2x-5)+6(2x+6) | | 1/3*6= | | z+-40=36 |